1984
DOI: 10.1111/j.1365-2621.1984.tb13683.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Protein Quality of Some Southern New England Marine Species

Abstract: Chemical composition, nutritional quality of protein and mineral content of cod, whiting, scup, squid and monkfish were determined. With a protein content ranging between 15 and 18%, the amino acid composition, in vitro enzymatic digestibility and PER evaluation indicated variation among two species. Protein quality of scup was significantly superior and that of squid was significantly inferior (p < 0.05) when compared to other species. The ratio of essential to nonessential amino acids ranged between a high o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 8 publications
7
13
2
Order By: Relevance
“…Moisture and total lipid contents ranged from 828 to 845 and 3.0 to 3.7 g kg À1 muscle (Table 2), respectively, in good agreement with the results reported in previous research carried out on angler muscle (Jhaveri et al, 1984;Barros-Velá zquez et al, 2008;García-Soto et al, 2011). Total lipid range can be considered low compared to the lipid ranges of other lean fish species such as hake (Merluccius merluccius) (Aubourg et al, 1999) and turbot (Psetta maxima) (Aubourg et al, 2007).…”
Section: General Composition Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…Moisture and total lipid contents ranged from 828 to 845 and 3.0 to 3.7 g kg À1 muscle (Table 2), respectively, in good agreement with the results reported in previous research carried out on angler muscle (Jhaveri et al, 1984;Barros-Velá zquez et al, 2008;García-Soto et al, 2011). Total lipid range can be considered low compared to the lipid ranges of other lean fish species such as hake (Merluccius merluccius) (Aubourg et al, 1999) and turbot (Psetta maxima) (Aubourg et al, 2007).…”
Section: General Composition Analysissupporting
confidence: 89%
“…Protein content ranged from 135 to 161 g kg À1 muscle (Table 2), in agreement with the contents reported by previous research on proximate composition of angler muscle (Jhaveri et al, 1984). Compared to most lean and fatty fish species, this range of protein contents can be considered relatively low, particularly for the head zone (Aitken et al, 1982;Piclet, 1987).…”
Section: General Composition Analysissupporting
confidence: 79%
See 2 more Smart Citations
“…Özyurt & Polat (2006) reported that the ratio of EAA to NEAA for wild sea bass were 0.75 and 0.77 for winter and summer respectively. According to other studies, the ratio of EAA to NEAA was 0.71 for cod Gadus morhua (Jhaveri et al, 1984) and mullet Mugil cephalus (Iwasaki & Harada, 1985); 0.74 for herring Clupea pallasi and 0.75 for chum salmon Oncorhynchus keta (Iwasaki and Harada, 1985). Similar ratios were obtained by and Valente et al (2011) in fillets of sea bream from other Mediterranean Regions in Europe.…”
Section: Amino Acid Content Of Sea Basssupporting
confidence: 65%